Shelter Distribution and Type Affect Space Use of a Desert Reptile - Roy C. Averill‐Murray; J. Daren Riedle (Ecology and Evolution)
ABSTRACT Animal home ranges derive from the distribution of resources across the landscape. For example, home ranges of most tortoise species in the United States revolve around networks of burrows. However, human disturbances that damage shelters can decrease habitat suitability, individual survival, and population persistence. We investigated effects of burrow distribution and availability on space use of the Sonoran Desert Tortoise Gopherus morafkai at two populations with different habitat structures to determine the extent to which habitat capacity is defined by factors subject to management, such as vegetation, relative to more permanent features such as rock shelters. We also demonstrated the superiority of autocorrelated kernel density estimation, illustrating flawed conclusions that could arise from the use of traditional home‐range estimators. Home‐range size increased with the number of available burrows at both sites. At the Florence Military Reservation (FMR), with numerous caliche caves and few rock burrows, larger home ranges effectively compensated for one third the burrow density as that of Sugarloaf Mountain, which predominantly featured rock burrows. Female tortoises had smaller home ranges than males despite having similar burrow densities. Females revisited individual burrows more often than males at Sugarloaf, which may relate to female use of preferred nesting sites; however, lower availability led males to revisit burrows at similar rates as females at FMR. Pairs of tortoises at FMR shared 72% more burrows than pairs at Sugarloaf, and pairs of females shared 33% fewer burrows than female–male pairs across both sites. Space and burrow use at FMR and Sugarloaf are consistent with predictions of how animals choose patches for their home ranges in ways that are optimal with respect to spatially distributed resources. Populations largely reliant on pallets or soil burrows may be more subject to declines due to anthropogenic impacts from grazing or off‐highway vehicle use or due to increasing temperatures.